2016
DOI: 10.1634/theoncologist.2015-0424
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Congestive Heart Failure in Early Breast Cancer Patients Undergoing Adjuvant Treatment With Trastuzumab: A Meta-Analysis

Abstract: Background. The use of trastuzumab has proven to be a successful strategy in patients with human epidermal growth factor receptor 2 (HER2)-positive breast cancer; however, it is associated with an increased risk of cardiac dysfunction. We performed an up-to-date, comprehensive meta-analysis to clarify the risk of congestive heart failure (CHF) in patients with early breast cancer receiving different durations of adjuvant trastuzumab with the longest-term follow-up. Methods. Eligible studies included randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…We updated the previous meta-analyses by including new and latest RCTs with the longest follow up period report to date [28][29][30][31]35]. Our results were consistent with the results of previous meta-analyses [14][15][16][17][18][19][20] which showed risk reduction for death and recurrence by about 30% to 34% and 36% to 50%, respectively. Likewise, our pooled results showed increasing risk of CHF and LVEF decline by about 3.71 and 2.17 times, respectively, which corresponded with previous meta-analyses results of 2.45 to 7.60 times for CHF and 1.88 to 2.45 times for LVEF decline.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We updated the previous meta-analyses by including new and latest RCTs with the longest follow up period report to date [28][29][30][31]35]. Our results were consistent with the results of previous meta-analyses [14][15][16][17][18][19][20] which showed risk reduction for death and recurrence by about 30% to 34% and 36% to 50%, respectively. Likewise, our pooled results showed increasing risk of CHF and LVEF decline by about 3.71 and 2.17 times, respectively, which corresponded with previous meta-analyses results of 2.45 to 7.60 times for CHF and 1.88 to 2.45 times for LVEF decline.…”
Section: Discussionsupporting
confidence: 82%
“…As for our knowledge, there were seven meta-analyses (N = 4-6 randomized controlled trials, RCTs) [14][15][16][17][18][19][20] and three systematic reviews only (N = 5-6 RCTs) [21][22][23]. Results of the seven metaanalyses [14][15][16][17][18][19][20] indicated that adjuvant trastuzumab with chemotherapy in treating HER2-positive EBC patients significantly improved the OS and DFS when compared to chemotherapy alone with a reduction in the risk of mortality ranging from about 30% to 34%, and a reduction in the risk of recurrence ranging from 34% to 50%. However, none of them comprehensively explored which prognostic factors (i.e., cycle regimen, type of administration, and the combined chemotherapy type) might affect both the relative treatment efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant decline in LVEF was more common AC-DH group than the TCH group (18.6% vs. 9.4%, p<0.001), with a rate of 11.2% in the AC-D group (28). A subsequent meta-analysis of adjuvant treatment trials (n=18,111) confirmed that adjuvant trastuzumab is associated with an increased risk of grade 3 and 4 CHF [RR 3.04 (95 % CI 1.12 to 7.85; p<0.00001)], but absolute rates are still low (29). The majority of episodes of LVEF decline do not progress to clinical CHF, instead resolving quickly after cessation of therapy (often with medical intervention).…”
Section: Incidence Timing and Risk Factors For Trastuzumab-related mentioning
confidence: 99%
“…Left ventricular systolic dysfunction is the most concerning cardiac toxicity associated with trastuzumab, particularly when it is administered in combination with an anthracycline [7]. Adjuvant clinical trials of trastuzumab have reported severe heart failure in 1.44-4% of patients; the overall risk ratio (RR) of high-grade heart failure was reported to be 3.04-fold higher with trastuzumab than without [9,10]. Moreover, up to 19% of patients were reported to have developed a significant decline in left ventricular ejection fraction (LVEF) [9,11].…”
Section: Introductionmentioning
confidence: 99%